A single detector energy-resolved proton radiography system: a proof of principle study by Monte Carlo simulations. (16th January 2019) - Huo, Wanli; Zwart, Townsend; Cooley, James; Huang, Kai; Finley, Caitlin; Jee, Kyung-Wook; Sharp, Gregory C; Rosenthal, Stanley; Xu, X George; Lu, Hsiao-Ming
Abstract: Taking advantage of Bragg peak and small spot size, pencil beam scanning proton therapy can deliver a highly conformal dose distribution to target while sparing normal tissues. However, such dose distributions can be highly sensitive to the proton range uncertainty which can reach 5% or higher in lung tissue. One proposed method for reducing range uncertainty is to measure the water equivalent path length (WEPL) by proton radiography. In this study, we followed a newly proposed proton beam radiography technique based on energy resolved dose functions (ERDF) to construct a Monte Carlo model for a single detector energy-resolved proton radiography system (SDPRS). This SDPRS model was constructed in the Monte Carlo software package TOPAS (TOol for PArticle Simulation) and it includes the Mevion HYPERSCAN ™ pencil beam scanning treatment head and a 2D dose detector positioned downstream as the imager. A calibration phantom containing a number of tissue equivalent materials was simulated to evaluate the accuracy in WEPL measurement by SDPRS. The mean deviation of the obtained relative stopping power (RSP) from the reference values was 0.31%. Proton radiographs of an anthropomorphic head phantom were also generated to demonstrate the clinical relevance of the technique. Effects of different energy layer spacing and measurement noise were also studied.